Ce3+/Ho3+ doped LaPO4 nanomaterials produced by hydrothermal technique for luminescence studies using ethylene glycol (EG) - Koneru, Girija Venkateswara; Putta, Venkata Nagendra Kumar; Bandi, Sirisha (Chemical Data Collections, 2024)
Using the Hydrothermal technique, a series of trivalent Ce3+/Ho3+co-doped LaPO4 nanophosphors were synthesised and exhibited good luminous qualities in both the (UC) and (DC) regimes. At 279–300 nm excitation, DC peaks at 365 nm, 460, 542, and 650 nm were seen, along with a minor non-radiative resonance energy transfer and a highly hazy P-O Charge Transfer (CT) band of Ho3+ions. We find that the (UC) nanophosphor LaPO4: Ce3+/Ho3+allows a strong 980 nm laser stimulation, causing the UC emission spectra to exhibit prominent Ho3+ ion resulting in peaks at 460, 542 and 650 nm as well as weak emission peaks at 300–360 nm. Future applications for these co-doped Ce3+ and Ho3+ ion monoclinic LaPO4 nanocrystals are anticipated to include better optical materials. Ultimately, many potential uses in various industries, from sophisticated display technologies to biomedical imaging and beyond, are made possible by the production and characterisation of co-doped Ce3+/Ho3+ ion nanophosphors in LaPO4 matrices. The realisation of useful systems and technologies utilising the special qualities of these nanocrystals may result from more study and development in these fields. [Display omitted]